2014
DOI: 10.3906/bot-1312-13
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous proline and proline-enriched Lolium perenne leaf extract protects against phytotoxic effects of nickel and salinity in Pisum sativum by altering polyamine metabolism in leaves

Abstract: IntroductionProline is a proteinogenic amino acid, highly essential for various vital metabolic processes within the plant tissues. It is naturally present in plants, microbes, and animals (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 79 publications
(79 reference statements)
5
33
0
Order By: Relevance
“…Likewise, Ashraf and Foolad (2007) reported that the effectiveness of PRO applied as a foliar spray depended on the concentration, time of application, type of species, and plant developmental stage. Shahid et al (2014) recorded that the effect of exogenous PRO on stress damages was dependent on the concentration, and foliar-applied PRO at a low concentration reduced the oxidation of lipid membranes in Pisum sativum under salinity-stressed conditions. In our study, to the best of our knowledge, it has been shown for the first time that exogenous PRO application in rooting medium and seed soaking modes alleviated the hazardous effects of drought stress on membranes in maize plants.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Ashraf and Foolad (2007) reported that the effectiveness of PRO applied as a foliar spray depended on the concentration, time of application, type of species, and plant developmental stage. Shahid et al (2014) recorded that the effect of exogenous PRO on stress damages was dependent on the concentration, and foliar-applied PRO at a low concentration reduced the oxidation of lipid membranes in Pisum sativum under salinity-stressed conditions. In our study, to the best of our knowledge, it has been shown for the first time that exogenous PRO application in rooting medium and seed soaking modes alleviated the hazardous effects of drought stress on membranes in maize plants.…”
Section: Discussionmentioning
confidence: 99%
“…In another experiment, pea plants were exposed to NaCl and/or NiCl 2 stress to investigate whether pure Pro or Pro enrichedleaf extract of Lolium perenne L. could effectively protect against phytotoxicity. Natural Pro (leaf extract) containing other essential nutrients proved to be a better protecting agent than pure Pro by altering the polyamine metabolism (Shahid et al, 2014). 7.5.…”
Section: Heavy Metal Toxicitymentioning
confidence: 99%
“…Pea is the fourth most important grain legume crop of the world, as measured by production (441.53 × 10 3 t) [Shahid et al 2014[Shahid et al , Šlosár et al 2016. Biofortification, the process of transferring nutrients into food crops, provides a comparatively cost-effective, sustainable, and long-term means of delivering more micronutrients [Saltzman et al 2013].…”
Section: Introductionmentioning
confidence: 99%